The dark places of business enterprise : reinstating social costs in institutional economics - Frigato, Pietro; Santos Arteaga, Francisco J., 1976- (New York : Routledge, 2019)
This book considers Thorstein Veblen's central preoccupation with the dark places of business enterprise, an integral part of the old institutional economics. Combining the contributions made by Karl William Kapp and Philip Mirowski, it proposes the systematization of an adjourned institutional theory of social costs of business enterprise useful for the analysis of contemporary crises. The Dark Places of Business Enterprise explores the research potential of the theory of social costs for the analysis of actual business behavior in the current globalized privatization regime. It begins with a detailed outline of Veblen's critique of business enterprise and market competition before illustrating the methodical enrichment of this approach through Kapp's work. Finally, it concludes by proposing the integration of the Veblenian-Kappian approach with Mirowski's theory of markets and business doubt manufacture. The resulting theory of social costs will shed light on the ubiquitous business control of society under the now dominant computer-based technological infrastructure. This interdisciplinary foundation of the theory of social costs, encompassing knowledge from computer science and engineering to natural sciences, provides the tools required to analyze this great transformation.
Introduction: critical institutionalism, market model failure and the business control of society through cybernetic manipulation -- Veblen's dark places of business enterprise and the theory of social costs -- Karl William Kapp's critical theory of social costs : asset-specific cost-shifting, retardation of efficiency and the paradox of social control -- Neoclassical economics beyond externalities? : Akerlof and Shiller's phishing for phools and the theory of social costs -- Digging into the dark places of business enterprise : revisiting the theory of social costs in the light of Mirowski's institutional economics of knowledge -- The darkest place of business enterprise : business surveillance, the financial crisis and the swansong of the market in the information age -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Externalities (Economics); Institutional economics; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History